Premyelinating Oligodendrocytes: Mechanisms Underlying Cell Survival and Integration - Hughes, Ethan G.; Stockton, Michael E. (Frontiers in Cell and Developmental Biology, 2021)
In the central nervous system, oligodendrocytes produce myelin sheaths that enwrap neuronal axons to provide trophic support and increase conduction velocity. New oligodendrocytes are produced throughout life through a process referred to as oligodendrogenesis. Oligodendrogenesis consists of three canonical stages: the oligodendrocyte precursor cell (OPC), the premyelinating oligodendrocyte (preOL), and the mature oligodendrocyte (OL). However, the generation of oligodendrocytes is inherently an inefficient process. Following precursor differentiation, a majority of premyelinating oligodendrocytes are lost, likely due to apoptosis. If premyelinating oligodendrocytes progress through this survival checkpoint, they generate new myelinating oligodendrocytes in a process we have termed integration. In this review, we will explore the intrinsic and extrinsic signaling pathways that influence preOL survival and integration by examining the intrinsic apoptotic pathways, metabolic demands, and the interactions between neurons, astrocytes, microglia and premyelinating oligodendrocytes. Additionally, we will discuss similarities between the maturation of newly generated neurons and premyelinating oligodendrocytes. Finally, we will consider how increasing survival and integration of preOLs has the potential to increase remyelination in multiple sclerosis. Deepening our understanding of premyelinating oligodendrocyte biology may open the door for new treatments for demyelinating disease and will help paint a clearer picture of how new oligodendrocytes are produced throughout life to facilitate brain function.